MEMBANGUN DUNIA KECIL DENGAN PROJECT BASED LEARNING (PjBL): KAJIAN LITERATUR TENTANG PROYEK DI PAUD - Panglipur, Diana Wahyu; Asmaroini, Ambiro Puji (LPPM Universitas Bina Bangsa, 2025)
Current passive learning methods are insufficient to prepare students for an ever-evolving world. Therefore, teaching staff must strive to create a conducive learning environment for their students. Amid this rapid development, a learning method, often called Project Based Learning (PjBL), better known as Project Based Learning, has been created. Project Based Learning (PjBL) is a learning approach that makes students the centre of learning. This article aims to analyse the benefits of Project Based Learning (PjBL) in early childhood, and its implementation in learning. The type of research used is qualitative with a literature review method. The results are that PjBL can increase creativity, a clean and healthy lifestyle, critical and creative thinking skills, visual-spatial intelligence, and students' social skills. PjBL can also help students develop collaboration skills, initiative and independence. PjBL provides direct experience in solving problems and finding useful solutions. Implementing PjBL in early childhood learning can be done through several stages and strategies, such as determining relevant topics, designing projects, preparing learning plans, implementing projects, reflection and evaluation. This article discusses several theories related to PjBL, such as constructivism, social learning theory, collaborative learning, problem-based learning, and project-based learning